2003
DOI: 10.1021/np030248c
|View full text |Cite
|
Sign up to set email alerts
|

15,21-Cyclowithanolides from Jaborosa bergii

Abstract: Six new withanolides (1-6) were isolated from the aerial parts of Jaborosa bergii plants and characterized by spectroscopic methods (1D and 2D NMR, MS). Five of the new compounds presented a novel norbornane-type structure in ring D of the steroid nucleus (1-5), resulting from a carbon-carbon bond between C-15 and C-21. The sixth withanolide isolated was the 5alpha-chloro-6beta-hydroxy analogue (6) of 2,3-dehydrojaborosalactol M (7), previously isolated from this plant. Compound 1 showed selective phytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 9 publications
2
31
0
Order By: Relevance
“…The species of Jaborosa are frequently rhizomatous perennial herbs (except J. bergii and J. sativa , which are annual or biennial), hemicryptophytes, or geophytes. Chemical screenings of several of them have revealed the presence of withanolides, which are promising steroid compounds with antitumoral activity (Mísico et al ., 1997, 2002; Anjaneyulu, Rao & Lequerne, 1998; Nicotra et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The species of Jaborosa are frequently rhizomatous perennial herbs (except J. bergii and J. sativa , which are annual or biennial), hemicryptophytes, or geophytes. Chemical screenings of several of them have revealed the presence of withanolides, which are promising steroid compounds with antitumoral activity (Mísico et al ., 1997, 2002; Anjaneyulu, Rao & Lequerne, 1998; Nicotra et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…14β-Hydroxywithanolide named physagulin I (18) has been isolated from Physalis species, and has an α-oxygenated function at position 15 (Nagafuji et al, 2004), and other 14β-hydroxywithanolide named jaborosalactol 23 (19) has been isolated from the flowering plant in the family Solanaceae, the nightshades, Jaborosa bergii (Nicotra et al, 2003). Nicotra and co-authors (2006) reported the isomeric clorohydrin, jaborosalactone 37 (20) from Jaborosa rotacea, and jaborosalactone T (21) was isolated from Jaborosa sativa (synonym Trechonaetes sativa) collected in Argentina (Bonetto et al, 1995).…”
Section: Chlorinated Plant Steroidsmentioning
confidence: 99%
“…It is worth mentioning that 17b-OH effects the C-20 configuration based on CIP (Ramacciotti and Nicotra 2007). If C-16 is substituted by a ketone group (C=O), then the C-20 absolute configuration was also deduced from the NOESY spectrum based on correlations between Me-18/H-12 and H-20/H-12 (Yokosuka et al 2003;Nicotra et al 2003). Researchers also have determined the C-20 absolute configuration in the light of correlations from H-14, H-17 to Me-21 (Zhang et al 2009).…”
Section: Absolute-configurationmentioning
confidence: 99%